MOLECULAR DOCKING AND ADMET PROPERTIES OF NOVEL 5-METHYL-6AH-BENZO [4, 5] OXAZOLO [3,2-A]QUINOLIN-2-OL DERIVATIVES FOR THEIR ANTI-CANCER ACTIVITY - MEHTA, SIMPI; KASWAN, POONAM; RANJAN, POOJA; SUDESH (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to design and evaluate a series of novel 5-Methyl-6aH-benzo [4,5]oxazolo [3,2-a]quinolin-2-ol derivatives as potential anticancer agents targeting the human amine oxidase (AO) enzyme. Methods: Seventeen oxazole-based ligands were designed and subjected to molecular docking simulations using the crystallographic structure of human AO (PDB ID: 2v5z). GlideScore was used to assess binding affinity, and key molecular interactions were analyzed. Additionally, ADME-Toxicity properties were predicted to evaluate pharmacokinetic and safety profiles. Results: Among the ligands, compounds 8 and 10 demonstrated the highest binding affinities, with GlideScores of –10.219 and –10.461 kcal/mol, respectively, significantly better than the reference drug R-(–)-Deprenyl (–6.205 kcal/mol). These ligands exhibited strong hydrophobic and π–π stacking interactions with active site residues PHE168, TRP119, and TYR435, indicating stable binding. ADME-Toxicity analysis revealed that all designed ligands had favorable pharmacokinetic profiles, including high oral absorption, low predicted toxicity, and acceptable blood-brain barrier permeability. Conclusion: The results highlight the therapeutic potential of oxazole derivatives as effective scaffolds for developing new anticancer agents targeting amine oxidase, with compounds 8 and 10 emerging as promising lead candidates.